2018
DOI: 10.1177/2041731418770909
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Printing in Maxillofacial Surgery: Hype versus Reality

Abstract: Three-dimensional printing technology is getting more attention recently, especially in the craniofacial region. This is a review of literature enlightening the materials that have been used to date and the application of such technology within the scope of maxillofacial surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…These synthetic models improve our understanding of preoperative anatomy in individual cases, allowing us to optimize our surgical approaches and introduce novel techniques tailored to a specific patient. This results in reduction of operative time, reduces surgical stress and minimizes perioperative errors [ 46 , 47 ]. In this clinical study, we reported five clinical cases assisted by 3D printing.…”
Section: Discussionmentioning
confidence: 99%
“…These synthetic models improve our understanding of preoperative anatomy in individual cases, allowing us to optimize our surgical approaches and introduce novel techniques tailored to a specific patient. This results in reduction of operative time, reduces surgical stress and minimizes perioperative errors [ 46 , 47 ]. In this clinical study, we reported five clinical cases assisted by 3D printing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ethical issues regarding 3D printed models should not be ignored. However, despite potential cost constraints, the prices of 3D printing equipment, materials, and software have been declining, [34,36] and more and more educational models of 3D printing are becoming learning tools for students [37]. Therefore, we hope that 3D printing models will play a role not only in surgery and communication but also in the anatomy classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, poly(εcaprolactone) (PCL) has been widely investigated, due to its slow degradation rate, for producing scaffolds, electrospun fibers or composites for cartilage TE, considering the slow rate of cartilage regeneration (Annabi et al, 2011;Garrigues et al, 2014;Legemate et al, 2016;Olubamiji et al, 2016). In addition to having excellent biocompatibility and adequate mechanical properties, it has been widely used for the production of complex structures by AM for craniofacial defects reconstruction (Aldaadaa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%